2020
DOI: 10.1111/zsc.12403
|View full text |Cite
|
Sign up to set email alerts
|

Multigene phylogeny reveals convergent evolution in small interstitial catfishes from the Amazon and Atlantic forests (Siluriformes: Trichomycteridae)

Abstract: Interstitial trichomycterid catfishes of the Glanapteryginae and Sarcoglanidinae with uncommon morphology have been known for long time from taxa endemic to the Amazon. In most recent decades, two genera, Listrura and Microcambeva, respectively, placed in Glanapteryginae and Sarcoglanidinae on the basis of morphological characters, have been described from the Atlantic Forest of eastern South America, about 1,500 km from the area inhabited by those Amazon taxa. Herein, we first test the phylogenetic positionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 58 publications
(201 reference statements)
2
40
0
Order By: Relevance
“…Microcambeva was recently assigned to the new sub‐family Microcambevinae as part of the multi‐locus molecular phylogenetic study by Costa et al . (2020), with further phylogenomic support for this classification from Ochoa et al . (2020).…”
Section: Introductionsupporting
confidence: 53%
“…Microcambeva was recently assigned to the new sub‐family Microcambevinae as part of the multi‐locus molecular phylogenetic study by Costa et al . (2020), with further phylogenomic support for this classification from Ochoa et al . (2020).…”
Section: Introductionsupporting
confidence: 53%
“…These data suggest a stronger tendency to losing pelvic fin in Cambeva than in these closely-related genera, but factors favouring this evolutionary event are still unknown. Amongst trichomycterids of the TSVSGM-clade (Costa and Bockmann 1994;Costa et al 2020a), parallel loss of pelvic fin and reduction or loss of other fins in the subfamilies Glanapteryginae and Microcambevinae have been related to their interstitial habits (Costa et al 2020a). On the other hand, conflicting field reports about the habitat of pelvic-less species of Cambeva do not indicate that they share similar habits.…”
Section: Discussionmentioning
confidence: 99%
“…camposi Miranda-Ribeiro, 1957, just by lacking pelvic fin (Miranda- Ribeiro 1949Ribeiro , 1957. However, morphological and molecular studies have consistently shown that E. candidus is a member of the genus Trichomycterus (Barbosa and Costa 2003;Katz et al 2018) and E. camposi belongs to the microcambevine genus Listrura de Pinna, 1988(de Pinna 1988Costa et al 2020a), therefore constituting independent evolutionary events of pelvic fin loss amongst trichomycterids.…”
Section: Introductionmentioning
confidence: 99%
“…Few morphological characters (Myers and Weitzman 1966;de Pinna 1989;de Pinna and Starnes 1990;Costa 1994;de Pinna and Winemiller 2000) have been described to diagnose Sarcoglanidinae and its genera. However, a recent molecular analysis directed to establish relationships of interstitial trichomycterids from the Atlantic Forest indicated that Sarcoglanidinae, in the sense of previous studies, is a polyphyletic assemblage comprising unrelated lineages with convergent morphological adaptations to the psammophilic life-style (Costa et al 2020). Currently, according to Costa et al (2020), Sarcoglanidinae comprises five genera: Malacoglanis Myers & Weitzman, 1966, Sarcoglanis Myers & Weitzman, 1966, Stauroglanis de Pinna, 1989, Stenolicmus de Pinna & Starnes, 1990, and Ammoglanis Costa, 1994 Ammoglanis was considered to be exclusively Amazonian, but recently, A. multidentatus Costa, Mattos & Santos, 2019 was described from northeastern Brazil, which expanded the geographical range of Ammoglanis 1000 km to the east (Costa et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent molecular analysis directed to establish relationships of interstitial trichomycterids from the Atlantic Forest indicated that Sarcoglanidinae, in the sense of previous studies, is a polyphyletic assemblage comprising unrelated lineages with convergent morphological adaptations to the psammophilic life-style (Costa et al 2020). Currently, according to Costa et al (2020), Sarcoglanidinae comprises five genera: Malacoglanis Myers & Weitzman, 1966, Sarcoglanis Myers & Weitzman, 1966, Stauroglanis de Pinna, 1989, Stenolicmus de Pinna & Starnes, 1990, and Ammoglanis Costa, 1994 Ammoglanis was considered to be exclusively Amazonian, but recently, A. multidentatus Costa, Mattos & Santos, 2019 was described from northeastern Brazil, which expanded the geographical range of Ammoglanis 1000 km to the east (Costa et al 2019). Three other species are currently recognized for the genus: Ammoglanis diaphanus Costa, 1994, from the Araguaia river basin; A. pulex from the Orinoco river basin; and Ammoglanis amapaensis Mattos, Costa & Gama, 2008 from the Jari river basin.…”
Section: Introductionmentioning
confidence: 99%